The Influence of Employee Behavior and Leadership Style on Performance Through Organizational Commitment at PT Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch - Aida Umi Fikri PA; Fadli Fadli; Beby Karina Fawzeea Sembiring (Riwayat: Educational Journal of History and Humanities, 2025)
In todays increasingly competitive business landscape, enhancing employee performance has become a strategic priority for organizations, including PT Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch. This study examines the influence of employee behavior and leadership style on performance, and how organizational commitment mediates these relationships. The research aims to analyze: (1) the direct effect of employee behavior on performance, (2) the direct effect of leadership style on performance, (3) the indirect effect of employee behavior on performance through organizational commitment, and (4) the indirect effect of leadership style on performance through organizational commitment. A quantitative, causal-associative approach was used. Data were obtained via questionnaires distributed to employees at PT Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch. The data were analyzed using Structural Equation Modeling (SEM) to evaluate direct and indirect effects and the mediating role of organizational commitment.Findings reveal that both employee behavior and leadership style significantly and positively affect performance. Moreover, organizational commitment acts as a significant mediator, strengthening the relationship between employee behavior and leadership style toward performance improvement. To improve employee performance, organizations should focus on fostering constructive employee behavior, implementing effective leadership, and reinforcing organizational commitment. These three elements are critical and should be integrated into the organizations human resource management strategy to ensure sustainable performance growth at PT Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch